1992
DOI: 10.1007/bf00008226
|View full text |Cite
|
Sign up to set email alerts
|

Impact of past management practices on the present status of the Muthupet mangrove ecosystem

Abstract: Muthupet mangrove ecosystem (loo 25' N and 79" 30' E) is located at the southern end of the Cauvery delta on the east coast of India. The swamp is characterized by the presence of only 4 species of exclusive mangroves namely Avicennia marina, Excoecaria agallocha, Aegiceras corniculatum and Acanthus ilicifolius.Community structure analysis carried out at four randomly selected quadrats showed that the relative density, relative dominance, relative frequency and importance value of A. marina was relatively hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
(1 reference statement)
0
6
0
Order By: Relevance
“…Standard botanical and silvicultural wisdom holds that Rhizophora spp. are poor at coppicing (Hamilton and Snedaker, 1984;Azariah et al, 1992;Hussain, 1995) and researchers who have done extensive surveys of mangroves in Australia and the Pacific -including sites subject to cutting -claim that coppicing in Rhizophora is highly unusual (Norman Duke and Katherine Ewel, personal communication).…”
Section: Effects Of Cutting On Forest Regenerationmentioning
confidence: 96%
See 1 more Smart Citation
“…Standard botanical and silvicultural wisdom holds that Rhizophora spp. are poor at coppicing (Hamilton and Snedaker, 1984;Azariah et al, 1992;Hussain, 1995) and researchers who have done extensive surveys of mangroves in Australia and the Pacific -including sites subject to cutting -claim that coppicing in Rhizophora is highly unusual (Norman Duke and Katherine Ewel, personal communication).…”
Section: Effects Of Cutting On Forest Regenerationmentioning
confidence: 96%
“…These studies found that R. mangle coppiced and grew from shoots poorly and, as a result, suffered greater mortality than did L. racemosa and A. germinans. Azariah et al (1992) believe that the effects of successive cutting on the Muthupet mangrove in India have been a gradual shift in forest composition towards species that coppice well (A. marina and E. agallocha) and away from species that do not (Rhizophora and Sonneratia).…”
Section: Effects Of Cutting On Forest Regenerationmentioning
confidence: 98%
“…Yet, such restrictions may have limited effect on actual cutting practices given the practical difficulties of monitoring sites that are remote and simultaneously accessible by land and sea (Dahdouh-Guebas et al, 2000bGlaser, 2003;Walters, 2003Walters, , 2005aLopez-Hoffman et al, 2006). Considerable research has been devoted to understanding the ecological effects of selection cutting and clear-felling as these treatments are applied in certain managed forests in Ecuador and South and Southeast Asia (Christensen, 1983a;FAO, 1985;Putz and Chan, 1986;Azariah et al, 1992;FAO, 1994;Nurkin, 1994;Blanchard and Prado, 1995;Hussain, 1995;Gong and Ong, 1995). But the relevance of this work is limited given that relatively little of the world's mangroves are subject to this kind of intensive forest management.…”
Section: Patterns and Consequences Of Forest Usementioning
confidence: 99%
“…and Bruguiera spp. (Putz and Chan, 1986;Blanchard and Prado, 1995;Hussain, 1995;Kairo et al, 2002; but see Azariah et al, 1992), the smaller openings created by selective cutting may better favor regeneration of species that successfully re-sprout/coppice from surviving stems, including Sonneratia spp., Avicennia spp., and Laguncularia racemosa (L.) Gaertn. f. (Smith and Berkes, 1993;Walters, 2005b; but see Pinzon et al, 2003).…”
Section: Patterns and Consequences Of Forest Usementioning
confidence: 99%
“…However, scientific understanding of the importance of the mangroves was realized earlier. The Ministry of Food and Agriculture of the Government of India conducted two symposia during 1956e1957 in form of the 9th Silvicultural Conference (1956) and the Mangrove Symposium (1957) where the ecological importance of the mangroves were highlighted (Azariah et al, 1992). Prior to that, some of the Indian mangroves were classified in any of the four categories as described in the forest policy of 1952.…”
Section: Existing Framework For Mangrove Management Indiamentioning
confidence: 99%